Corporate Brand Image of Islamic Bank in Malaysia: Antecedents and Consequence - Ab Hamid, Siti Ngayesah; Wan Jusoh, Wan Jamaliah; Maulan, Suharni (UUM Press, 2020)
The role of corporate brand image in influencing the survival of companies has never been underestimated. Because of this, this study intends to examine the antecedents and the consequence of corporate brand image towards customer behaviour. A model proposing firms and non-firms communication as the antecedents and loyalty as the consequence was proposed. One hundred and sixty-eight (168) questionnaires were collected and data was analysed based on the Partial Least Square-Structural Equation Modeling (PLS-SEM). The result of the study revealed that both firm and non-firm communication play a significant role in shaping the corporate brand image of an Islamic bank, especially in Malaysia. Corporate brand image on the other hand was also found to influence customers loyalty. These findings have broadened the understanding of the corporate brand images antecedents and the consequence also shows the importance of managing the Islamic bank corporate communication.